2019
DOI: 10.1002/hep.30810
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Fibroblast Growth Factor (FGF) 15 and FGF19 on Liver Fibrosis Development

Abstract: Farnesoid X receptor (FXR) induces fibroblast growth factor 15 (FGF15; human ortholog FGF19) in the gut to potently inhibit bile acid (BA) synthesis in the liver. FXR activation in hepatic stellate cells (HSCs) reduces liver fibrosis (LF). Fgf15–/– mice develop attenuated LF, but the underlying mechanisms for this protection are unclear. We hypothesized that FGF15/19 functions as a profibrotic mediator or mitogen to HSCs and increased BAs in Fgf15–/– mice leads to enhanced FXR activation in HSCs, subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 36 publications
2
48
0
Order By: Relevance
“…Many of FGF19 targets are related to metabolism and proliferation [23]. Several experiments have demonstrated that FGF19 exerts a protective effect against liver fibrosis [24][25][26][27]. Binding to FGFR4 is required for FGF19 proliferative function in mouse livers [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Many of FGF19 targets are related to metabolism and proliferation [23]. Several experiments have demonstrated that FGF19 exerts a protective effect against liver fibrosis [24][25][26][27]. Binding to FGFR4 is required for FGF19 proliferative function in mouse livers [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of FGFs to influence cell migration, the expression of Fgf15 along a potential migratory path of interneurons, and the regulation of Fgf15 expression by retinal input led us to hypothesize that FGF15 may be necessary for the recruitment of GABAergic interneurons into the neonatal visual thalamus. To test this, we employed Fgf15 −/− mutant mice, which lack functional FGF15, by deleting the entire third exon of the gene, which encodes for half of the protein, including the FGFRand heparin-binding motifs (50,51). While a significant fraction of Fgf15 −/− mutant mice die embryonically, some survive into adulthood (50,52).…”
Section: Retinal Inputs Are Necessary For Interneuron Recruitment Intmentioning
confidence: 99%
“…Activation of FXR induces SHP to increase the peroxisomal proliferator-activated receptor γ (PPARγ) expression in HSCs, and PPARγ is well-known to inactivate HSCs (71,72). Recently, we have shown that FGF15 deficiency reduces hepatic fibrosis through increasing FXR activation following loss of FGF15-mediated suppression of BA synthesis (73,74). Interestingly, in a human HSC cell line, LX2, FGF19 does not suppress fibrogenic gene expression, but suppresses inflammation, likely through modulating the inhibitor of nuclear factor kappa B (IκB) activity (74).…”
Section: Role In Inflammation and Fibrosismentioning
confidence: 99%
“…Recently, we have shown that FGF15 deficiency reduces hepatic fibrosis through increasing FXR activation following loss of FGF15-mediated suppression of BA synthesis (73,74). Interestingly, in a human HSC cell line, LX2, FGF19 does not suppress fibrogenic gene expression, but suppresses inflammation, likely through modulating the inhibitor of nuclear factor kappa B (IκB) activity (74). These studies provide another group of evidence to support the role of FXR as a homeostatic regulator to suppress liver inflammation and fibrosis.…”
Section: Role In Inflammation and Fibrosismentioning
confidence: 99%